Effect of a rapid thermal annealing process on the electrical properties of an aluminum‐doped indium zinc tin oxide thin film transistor. Issue 1 (12th September 2016) - Nam, Yunyong; Yang, Jong‐Heon; Jeong, Pilseong; Kwon, Oh‐Sang; Pi, Jae‐Eun; Cho, Sung Haeng; Hwang, Chi‐Sun; Ahn, Jeahan; Ji, Sanghyun; Park, Sang‐Hee Ko
Abstract : We report the effect of a rapid thermal annealing process (RTP) on the electrical properties of an aluminum‐doped indium zinc tin oxide (Al‐IZTO) thin film transistor (TFT) with a back‐channel etched (BCE) structure. First, the RTP temperatures were varied from 250 to 350 °C, and their effect on Al‐IZTO TFT was investigated. The 250 °C RTP produced the best transfer characteristics (subthreshold swing = 0.11 V/dec, hysteresis = −0.25 V, and mobility = 26.42 cm 2  V −1 s −1 ), and as the temperature increased, the TFTs showed slightly degraded properties in hysteresis and subthreshold swing. Through the transmission line method (TLM), the channel shortening effect and contact properties according to the annealing temperature were studied. The reliability against a negative gate bias stress under illumination (NBIS) was also analyzed. At high RTP temperature (>300 °C), stability under NBIS was considerably improved, and the 350 °C RTP device showed turn‐on voltage shift of −1.7 V. The microwave photoconductivity decay (μ‐PCD) method revealed that the RTP effectively reduced shallow localized states, which enhanced the NBIS stability at high temperature. Finally, the RTP was compared with the conventional furnace process at the same temperature in terms of transfer characteristics and uniformity. Even with a much shorter process time for the RTP, Al‐IZTO TFTs exhibited similar or better transfer properties and uniformity to or than the furnace annealing.